Pelatihan Penyusunan Instrumen Penelitian dalam Bimbingan dan Konseling bagi Mahasiswa BK sebagai calon Guru BK dan Konselor Sekolah - Maulita, Rizki; Ubaidillah, Muhammad; Nurzafira, Istiqomah (Nemui Nyimah, 2024)
Preparing original and relevant research instruments is an important skill for Guidance and Counseling (BK) Study Program students, especially for producing quality research. However, many students prefer to adapt existing instruments rather than compose their own. This affects the originality of the research and the relevance of the results to actual problems in the field. For this reason, training was held in preparing research instruments for BK students at Lampung University. Training methods include theory dissemination, instrument preparation simulations, and empirical testing. The results of the training show that students are able to compose research instruments independently. Each participant succeeded in producing one original research instrument that was relevant to their research topic. This training succeeded in improving students' practical skills and made a positive contribution to the development of research in the field of BK